Experimental Study on the Stress Sensitivity and Influence Factors of Shale under Varying Stress - Zhonghu Wu; Yujun Zuo; Shanyong Wang; Jibin Sunwen; Leilei Liu (Shock and Vibration)
Shale reservoirs are characterized by extremely low permeability and high clay content. To further study the stress sensitivity of a shale reservoir, the Lower Cambrian shale in north Guizhou was utilized. Through laboratory testing, the relationships between the shale porosity and permeability and the effective stress were established, and the stress sensitivity of shale was analysed. The mechanical properties and mineral composition of this shale were studied by rock mechanics testing and X-ray diffraction. The main factors affecting the stress sensitivity were analysed. The results show that the porosity and permeability of this shale decrease with increasing effective stress; the shale reservoir permeability damage rate is 61.44 ~ 73.93%, with an average of 69.92%; the permeability stress sensitivity coefficient is 0.04867 ~ 0.05485 MPa−1, with an average of 0.05312 MPa−1; and the shale reservoir stress sensitivity is strong. Shale stress sensitivity is related to the rock mineral composition and rock mechanical properties. The higher the clay content in the mineral composition, the lower the elastic modulus of shale, the higher the compressibility, and the greater the stress sensitivity coefficient.